2017
DOI: 10.22161/ijaems.3.12.9
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Corrosion Inhibition of Mild Steel in 0.5M Tetraoxosulphate (VI) acid by Alstonia boonei Leaves Extract as an Inhibitor at Different Temperatures

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…An inspection of the figures revealed that the corrosion rates increased with temperature. Similar trends were also obtained by Loto et al (2011) and Godwin -Nwakwasi et al (2017).…”
Section: Effect Of Temperature On Corrosion Ratesupporting
confidence: 90%
See 1 more Smart Citation
“…An inspection of the figures revealed that the corrosion rates increased with temperature. Similar trends were also obtained by Loto et al (2011) and Godwin -Nwakwasi et al (2017).…”
Section: Effect Of Temperature On Corrosion Ratesupporting
confidence: 90%
“…Plants are now being used as alternatives to chemicalbased corrosion inhibitors because they are cheap, ecologically friendly and renewable sources (Umoren et al, 2008). Several researchers have successfully used extracts from green plants to mitigate the corrosion of metals in various media (Molina -Ocampo et al, 2015;Fadare et al, 2016;Godwin-Nwakwasi et al, 2017;Khadom et al, 2018;Agi et al, 2018;Waidi et al, 2020;Izionworu et al, 2021;Oruene et al, 2021). Though many plants have been investigated for their anticorrosion inhibition capabilities, there are still many that have not been studied for their corrosion inhibition potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The displacement indicates that SCLE acts as a mixed-type inhibitor that hinders both anodic and cathodic reactive sites due to the electroactive components of the inhibitor being adsorbed across the API 5L surface [37,38]. In addition, shifting potential corrosion is less than -85 mV from the blank to the anodic or cathodic directions; inhibitors can be classified as mixed-type inhibitors [39,40]. The displacement of potential corrosion was all less than -85 mV.…”
Section: Discussion Of Syzygium Cumini As a Green Corrosion Inhibitormentioning
confidence: 99%